Retrospective Study of Salvage Dose-Escalated Intensity-Modulated Radiation Therapy in Radiotherapy-naïve, Non-metastatic, Castration-Resistant Prostate Cancer - Thonglert, Kanokphorn; Ditjarern, Pimpawee; Amornwichet, Napapat; Alisanant, Petch; Khorprasert, Chonlakiet (Journal of Thai Association of Radiation Oncology, 2022)
Backgrounds: The role of salvage dose-escalated intensity-modulated radiation therapy (IMRT) for radiotherapy-naïve, non-metastatic, castration-resistant prostate cancer (nmCRPC) is controversial. Objectives: This retrospective study reports the clinical outcomes of salvage dose-escalated IMRT in radiotherapy-naïve, nmCRPC. Materials and methods: We retrospectively evaluated 22 patients with nmCRPC treated with salvage dose escalated IMRT between March 2009 and June 2019. The primary outcome was biochemical relapse-free survival (BRFS). The secondary outcomes were clinical progression-free survival (CPFS), metastasis-free survival (MFS), overall survival (OS), prognostic factors, and toxicities. Results: The median follow-up was 43 months. The mean age at the time of salvage IMRT was 73.8 years. The median PSA prior to salvage IMRT was 6.68 ng/ml. All patients received dose-escalated IMRT 76-80 Gy to prostate and seminal vesicles. The median BRFS was 31 months, with a 5-year BRFS of 43.6%. The median CPFS was 37 months, with a 5-year CPFS of 47.4%. The median MFS was not-reach with a 5-year MFS of 50.6%. The 5-year OS was 62.4%, with a median OS of 73 months. In multivariate analysis, the PSA prior to EBRT was the only significant prognostic factor for better BRFS and CPFS. Grade 3-4 late gastrointestinal (GI) and genitourinary (GU) toxicities were 4.5% and 0%, respectively. Conclusion: In radiotherapy-naïve patients with nmCRPC, salvage dose-escalated IMRT was a feasible treatment option with acceptable toxicity.